2015
DOI: 10.3109/13651501.2015.1016972
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional alcoholism typologies: could they guide clinical practice? Results from a 3-month prospective study

Abstract: Our findings point to the need to differentiate multidimensional alcoholism subtypes before planning the clinical management of alcohol use disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…Higher scores on SADQ indicate a greater level of alcohol dependence. Previous studies have showed good psychometric properties in a sample of Portuguese alcohol‐dependent patients …”
Section: Methodsmentioning
confidence: 95%
See 4 more Smart Citations
“…Higher scores on SADQ indicate a greater level of alcohol dependence. Previous studies have showed good psychometric properties in a sample of Portuguese alcohol‐dependent patients …”
Section: Methodsmentioning
confidence: 95%
“…Psychiatric disorders from the impulsive spectrum share similarities with cyclothymia features. The tendency to this alternating pattern of emotional highs and lows increases the likelihood to act impulsively, to use immature defence mechanisms (like acting out) and to have low self‐directedness, all of which are known predictors of abstinence violation . Patients with poor judgment about their own ability to reach goals and to deal with reality, in combination with emotional volatility, are particularly prone to experience craving and to act on craving rather than controlling it and therefore tend to relapse .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations